Validation of HITEMP-2010 for carbon dioxide and water vapour at high temperatures and atmospheric pressures in 450–7600 cm−1 spectral range. (May 2015) - Alberti, Michael; Weber, Roman; Mancini, Marco; Fateev, Alexander; Clausen, Sønnik
Abstract: The objective of the work is validation of HITEMP-2010 at atmospheric pressures and temperatures reaching 1770 K . To this end, spectral transmissivities at 1 cm −1 resolution and excellent signal-to-noise-ratio have been measured for 22 CO 2 / H 2 O / N 2 mixtures. In this paper we consider the 450 cm −1 –7600 cm −1 spectral range. The LbL calculations and their comparison with the measured spectra have clearly shown that HITEMP-2010 is an excellent database (superior to previous versions) for calculating emissivities and absorption coefficients for CO2 and H 2 O molecules in the 500–1770 K range. Several absorption lines listed in HITEMP-2010 have not been observed in the measured spectra and/or are wrongly scaled with temperature. The complete (there are no missing bands) spectra spanning the 450 – 7600 cm − 1 range are appended as Supplementary Material. Abstract : Highlights: High resolution transmissivity data have been generated for CO2 /H2 O/N2 mixtures. Temperatures are in the 500–1770 K range. Measurements are available as Supplementary Material. HITEMP-2010 has been used to reproduce the measured data. HITEMP-2010 has proven to be an excellent database.